The Role of Commitment Devices in Budgeting. (14th April 2014) - Schwartz, Steven T.; Spires, Eric E.; Wallin, David E.; Young, Richard A.
<x xml:space="preserve">Abstract</x> We administer an experiment to investigate a commitment device in the form of an unobservable commitment regarding a superior's acceptance rule for a subordinate's budget request. We find that unobservable commitment, when exogenously imposed, diminishes superiors' propensity for costly norm enforcement. The results for an endogenous treatment are similar except that those superiors who choose unobservable commitment only occasionally use the commitment device in a manner consistent with norm enforcement. Our interpretation of the results is that unobservable commitment decreases the emotional response to unfair behavior and that information asymmetry accentuates this effect. Copyright © 2014 John Wiley & Sons, Ltd.